Trace metals in muscle, liver and gill tissues of marine fishes from Mersing, eastern coast of Peninsular Malaysia: concentration and assessment of human health risk - Fathi, H. B.; Othman, Mohammad Shuhaimi; Abd. Ghaffar, Mazlan; Arshad, Aziz; Nurul Amin, Sarker Mohammad; Das, Simon Kumar (Academic Journals, 2013)
Trace metals (Cu, Zn, Cd and Pb) concentrations in muscles, livers and gills of three important marine fishes, Torpedo Scad (Megalaspis cordyla), Sea Catfish (Arius thalassinus) and Belangeri Croaker (Johnius belangeri) were studied using the Inductively Coupled Plasma Mass Spectrometry (ICP-MS). The samples were collected from Mersing the eastern coastal waters of Peninsular Malaysia. The estimated ranges of Cu, Zn, Cd and Pb concentrations in the muscles, livers and gills of the three fish species were 1.51-3.48, 17.54-28.34, 0.02-0.12 and 0.12-0.15; 15.8-26.0, 80.58-365.1, 2.32-6.14 and 0.57-1.54; 3.04-5.51, 61.63-259.3, 0.03-0.12 and 0.14-2.03 μg g-1 dry weight, respectively. Metal concentrations in the edible parts of the fish were assessed for human consumption according to the Provisional Tolerable Weekly Intake (PTWI) and Provisional Tolerable Daily Intake (PTDI). Generally, levels of metal in muscles were lower than those in livers and gills. Zinc concentration was found to be the highest among the tested metals in all three species. The estimated weekly and daily intakes for the studied metals were far below the PTWI and PTDI limits. Present study reveals that consumption of these fishes from the study area does not pose a risk to human health.